Evaluating Starter Feeding on Ruminal Function in Yak Calves: Combined 16S rRNA Sequencing and Metabolomics - Wang, Yin; Xia, Hongze; Yang, Qien; Yang, Deyu; Liu, Shujie; Cui, Zhanhong (Frontiers in Microbiology, 2022)
For young ruminants, starter feeding can effectively facilitate the growth and development of rumen in ruminants, but the development of rumen is an important physiological challenge as it remains unclear for the mechanism of starter feeding stimulating. Here, we performed an analysis of ruminal microbiota and their metabolites in yak calves to explore how the ruminal microbiota and their metabolites stimulate the ruminal function. We designed 2 experiments using 20 yak calves were assigned equally into 2 groups, based on feeding milk replacer; RA group was fed with alfalfa hay while the RAS group was fed with alfalfa hay and starter. After the experiment, we investigated the ruminal microbiota and metabolites through 16S rRNA sequencing and LC-MS-based metabolomics. During the pre-weaning period, the RAS group significantly promoted the growth performance and ruminal development in yak calves, including increases in body weight, chest girth and development of rumen (P < 0.05). The RAS group increased the relative abundance of Bacteroidota, Proteobacteria, Chloroflexi, Synergistota and Spirochaetota and decreased the abundance of Firmicutes, Desulfobacterota, Actinobacteriota and Actinobacteriota at the phylum level (P < 0.05). At the genus level, the rumen content of the RAS group was significantly enriched for Rikenellaceae_RC9_gut_group and Ruminococcus, while depleted for Prevotella, Christensenellaceae_R-7_group and NK4A214_group (P < 0.05). A total of 37 metabolites were identified between the RA group and the RAS group, 15 metabolites of which were up-regulated and 22 metabolites were down-regulated compared with the RA group. Metabolic pathway analyses indicated that up-regulated of the metabolites of the RAS group yak calves were related to carbohydrate metabolism and ubiquinone and other terpenoid-quinone biosynthesis, while the down-regulated metabolic pathway was relevant to xenobiotics biodegradation and metabolism and nucleotide metabolism. In summary, starter feeding before weaning significantly increased the dry matter intake and body weight of yak calves, changed the diversity and abundance of ruminal microbiota, and positively regulated the good development of ruminal morphology and function, providing an important basis for high-quality cultivation and the nutritional level of nutrition of yak calves in the Qinghai Tibet plateau.